Speckle contrast of interfering fluorescence X-rays - Trost, Fabian; Ayyer, Kartik; Oberthuer, Dominik; Yefanov, Oleksandr; Bajt, Saša; Caleman, Carl; Weimer, Agnes; Feld, Artur; Weller, Horst; Boutet, Sébastien; Koglin, Jason; Timneanu, Nicusor; et al. (Journal of Synchrotron Radiation, 2023)
With the development of X-ray free-electron lasers (XFELs), producing pulses of femtosecond durations comparable with the coherence times of X-ray fluorescence, it has become possible to observe intensity-intensity correlations due to the interference of emission from independent atoms. This has been used to compare durations of X-ray pulses and to measure the size of a focusedX-ray beam, for example. Here it is shown that it is also possible to observe the interference of fluorescence photons through the measurement of the speckle contrast of angle-resolved fluorescence patterns. Speckle contrast is often used as a measure of the degree of coherence of the incident beam or the fluctuations of the illuminated sample as determined from X-ray diffraction patterns formed by elastic scattering, rather than from fluorescence patterns as addressed here. Commonly used approaches to estimate speckle contrast were found to suffer when applied to XFEL-generated fluorescence patterns due to low photon counts and a significant variation of the excitation pulse energy from shot to shot. A new method to reliably estimate speckle contrast under such conditions, using a weighting scheme, is introduced. The method is demonstrated by comparing the speckle contrast of fluorescence observed with pulses of 3 fs to 15 fs duration.
CRIS-Team Scopus Importer:2023-01-13
Keywords: incoherent diffraction imaging; speckle contrast estimation; X-ray fluorescence; XPCS